THE INFLUENCE OF PVA.cl.CITRIC ACID/CHITOSAN MEMBRANE HYDROPHICILITY ON THE TRANSPORT OF CREATININE AND UREA - Retno Ariadi Lusiana; Dwi Siswanta; Mudasir Mudasir; Takashi Hayashita (Universitas Gadjah Mada, 2013)
The influence of cross-linking and membrane hydrophilicity on the transport rate had been studied using a membrane prepared from a mixture of chitosan/PVA cross-linked citric acid (PVA.cl.CA) for creatinine and urea transport. The optimum mole ratio of PVA:citric acid as well as the best composition of chitosan:PVA.cl.CA were determined using creatinine transport study. Using the optimum compositions, further study was done using different thickness of the membrane in transporting creatinine, urea and a mixture of 3 species (creatinine, urea and vitamin B12). Membrane characterization was done using FT-IR spectrophotometer, water absorption test, TG/DTG and SEM. The results showed that the optimum composition PVA:citric acid was obtained to be 90:1, having % WU of 113.74% and creatinine transport percentage of 18.16%. Meanwhile, the optimum composition of chitosan:PVA.cl.CA was found at 4:6 ratio having % WU and % transport of 136.67% and 24.26%, respectively. The optimum transport capacity was found for membrane thickness of 50 µm with WU% at 139.61% and the percent transport of creatinine and urea each was 38.93% and 60.36%. The presence vitamin B12 in the solution of is proved to disturb the transport of creatinine and urea through the membrane. Finally, hydrophilicity seemed to give substantial contribution in the transport process as well as the mechanical strength of the membrane.